Epidemiology and microbiology of catheter-associated urinary tract infections: A 14-year surveillance study at a tertiary care center in Lebanon - Abdel Hadi Shmoury; Wael Hanna; Johnny Zakhour; Nada Kara Zahreddine; Souha S. Kanj (Elsevier, 2024)
Background: Catheter-associated urinary tract infections (CAUTIs) are the most common device-associated healthcare-acquired infections and pose a significant burden on patients and healthcare systems worldwide. However, there is a paucity of data on CAUTI epidemiology and microbiology in the Middle East and North Africa (MENA) region, including Lebanon. Methods: This 14-year retrospective cohort study was conducted at a tertiary care center in Lebanon. It analyzed data on all adult patients diagnosed with CAUTI between January 2009 and December 2022 in intensive care units (ICUs) and between June 2011 and December 2022 in regular units. Incidence rates, urinary catheter utilization ratios, and microbiological profiles were collected and analyzed. Results: A total of 620 CAUTI cases were identified during the study period. The overall CAUTI rate was 2.4 per 1000 catheter-days, with higher rates in ICUs (3.2 per 1000 catheter-days) compared to regular units (1.4 per 1000 catheter-days). No significant changes in the rates were noted despite implementing many interventions. The most common pathogens were Gram-negative bacteria, with Escherichia coli, Pseudomonas aeruginosa, and Klebsiella pneumoniae being predominant. Multidrug-resistant organisms represented 48% of all isolates. Enterobacterales were largely extended-spectrum β-lactamase (ESBL) producing, and most Acinetobacter baumannii isolates showed multidrug resistance. Conclusions: This study provides important insights into CAUTI epidemiology and microbiology in a tertiary care center in Lebanon, addressing the knowledge gap in this area in the MENA region. Despite implementing prevention measures, CAUTI rates remained stable over the 14-year period. The findings highlight the need for continuous improvement in infection prevention practices, diagnostic stewardship, and antimicrobial stewardship, especially given the rising threat of antimicrobial resistance. These results can serve as a guide for the development of targeted preventive strategies to reduce the burden of CAUTIs, particularly in low- and middle-income countries where antimicrobial resistance is a major issue.